Ataxia caused by a single dose of dexketoprofen trometamol - Avcı, Sema; Genç, Selim; Aydın, Macit; Büyükcam, Fatih; Özkan, Seda (Acta Biomedica Atenei Parmensis, 2014)
Dexketoprofen trometamol is one of the non-steroid anti-inflamatory drugs (NSAID) used as an analgesic. Dexketoprofen drug treatment can lead to various adverse effects as follow: nausea, vomiting, gastrointestinal hemorrhage, acute kidney injury and neurologic side effects like headache, anxiety and dizziness. A 41 year-old-woman admitted to emergency department with speech disorder and loses her balance continued about two hours after the use of per oral dexketoprofen. The patient who kept under observation in emergency department was discharged about four hours later due to regression of clinical symptoms. We think that this is the first case report of ataxia after the use of per oral dexketoprofen in medical literature.